Novel Nitro-Heteroaromatic Antimicrobial Agents for the Control and Eradication of Biofilm-Forming Bacteria - Heidi N. Koenig; Gregory M. Durling; Danica J. Walsh; Tom Livinghouse; Philip S. Stewart (MDPI AG, 2021)
The synthesis and biological activity of several novel nitrothiazole, nitrobenzothiazole, and nitrofuran containing antimicrobial agents for the eradication of biofilm-forming Gram-negative and Gram-positive pathogens is described. Nitazoxanide (NTZ), nitrofurantoin, and furazolidone are commercial antimicrobials which were used as models to show how structural modification improved activity toward planktonic bacteria via minimum inhibitory concentration (MIC) assays and biofilms via minimum biofilm eradication concentration (MBEC) assays. Structure-activity relationship (SAR) studies illustrate the ways in which improvements have been made to the aforementioned antimicrobial agents. It is of particular interest in this regard that the introduction of a chloro substituent at the 5-position of NTZ (analog 1b) resulted in marked activity enhancement, as did the replacement of the 2-acetoxy substituent in the latter compound with a basic amine group (analog 7b). It is also of importance that analog 4a, which is a simple methacrylamide, displayed noteworthy activity against S. epidermidis biofilms. These lead compounds identified to have high activity towards biofilms provide promise as starting points in future pro-drug studies.